Human immunodeficiency virus-hepatitis C virus co-infection in pregnant women and perinatal transmission to infants in Thailand - Ngo-Giang-Huong N. (2014)
Objectives: The objectives of this study were to assess the prevalence and factors associated with hepatitis C virus (HCV) infection in human immunodeficiency virus (HIV)-infected and -uninfected Thai pregnant women and the rate of HCV transmission to their infants. Patients and methods: Study subjects included 1435 HIV-infected pregnant women and their infants, enrolled in a perinatal HIV prevention trial, and a control group of 448 HIV-uninfected pregnant women. Women were screened for HCV antibodies with an enzyme immunoassay. Positive results were confirmed by recombinant immunoblot and HCV RNA quantification. Infants were tested for HCV antibodies at 18 months or for HCV RNA at between 6 weeks and 6 months. Results: Of the HIV-infected women, 2.9% were HCV-infected compared to 0.5% of HIV-uninfected women (p = 0.001). Only history of intravenous drug use was associated with HCV infection in HIV-infected women. Ten percent of infants born to co-infected mothers acquired HCV. The risk of transmission was associated with a high maternal HCV RNA (p = 0.012), but not with HIV-1 load or CD4 count. Conclusions: Acquisition of HCV through intravenous drug use partially explains the higher rate of HCV infection in HIV-infected Thai women than in HIV-uninfected controls. Perinatal transmission occurred in 10% of infants of HIV-HCV-co-infected mothers and was associated with high maternal HCV RNA. © 2009 International Society for Infectious Diseases.